Appplication of Biochar and Rice Husk Ash to sulfur Absorption, Growth and Production of Shallots Plant (Allium ascalonicum L.) - Sri Pratiwi Aritonang; Ebsan Marihot Sianipar; Efbertias Sitorus; Pahala LL Sianturi (Postgraduate, University of Mataram, 2025)
Soil fertility decline and sulfur deficiency are major constraints in shallot (Allium ascalonicum L.) cultivation, especially in sandy soils with low cation exchange capacity. Biochar and rice husk ash are potential soil amendments known to improve soil structure, nutrient availability, and crop productivity. This study aimed to determine the effect of rice husk biochar and rice husk ash on the growth, yield, and sulfur uptake of shallots. A factorial experiment was conducted using a Randomized Group Design (RGD) with two factors: biochar and rice husk ash, each at three dose levels. Results showed that biochar application improved the number of leaves, number of tillers, and bulb weight per unit, while rice husk ash had a limited effect, mainly enhancing leaf number at early growth. No significant interaction between the two amendments was observed across measured parameters, including sulfur uptake. These findings suggest that biochar contributes more effectively to shallot growth and yield than rice husk ash under the tested conditions. Further studies are recommended to optimize the combined use of organic amendments and to explore their long-term effects on soil nutrient dynamics and crop performance.